The Effect of Wet Cupping on Recovery Rate and Its Impact on the Concentration Levels of Certain Essential Blood Components: A Comparative Study on Middle- and Long-Distance Runners Aged 18–24 in Souk Ahras Province. - رواينية , حمدي; محفوظي , محمود (Journal of Sport Science Technology and Physical Activities, 2026)
This study aims to identify the potential positive effects of wet cupping on the recovery rate of middle- and long-distance runners in Souk Ahras Province, aged 18–24 years. For this purpose, a quasi-experimental approach was adopted on a sample of 12 participants selected randomly. Data were collected using both the FNS laboratory test and the Navette field test. After data collection and statistical analysis, a positive effect of cupping on certain blood components was observed, and consequently on the recovery rate. Based on these findings, the study recommends incorporating cupping into athletes’ recovery programs.